Changes in ocular biometry during short‐term accommodation in children. (12th July 2020) - Hughes, Rohan P J; Read, Scott A; Collins, Michael J; Vincent, Stephen J
Abstract: Purpose: Near work has been linked with myopia development; however, the underlying mechanism remains unclear. Small increases in axial length during accommodation have previously been reported in adults, and therefore, this study aimed to examine if accommodation‐induced changes in ocular biometry also occur in school‐aged children. Methods: A range of ocular biometric measurements were captured during brief accommodation tasks at four demands (0, 3, 6, and 9 D), in a group of 87 non‐myopic, school‐aged children using a Badal optometer mounted to a non‐contact optical biometer (Zeiss IOLMaster 700, https://www.zeiss.com/meditec/int/product‐portfolio/optical‐biometers/iolmaster‐700.html ). Reliable biometry measurements and active accommodation were observed for 76 participants who were included in the analysis. The average central corneal thickness (CCT), anterior chamber depth (ACD), crystalline lens thickness (LT), anterior segment length (ASL), vitreous chamber depth (VCD), and axial length (AL) were determined for each accommodation demand. Raw measurements of AL and VCD were corrected to account for the effect of LT changes during accommodation. Results: On average, AL increased with increasing levels of accommodation ( p = 0.005). The mean (SEM, standard error of the mean) AL increase from 0 D to the 3, 6, and 9 D demands was 4 (1), 8 (1), and 15 (2) µm, respectively. All other biometric parameters, except CCT, changed significantly during accommodation. LT and ASL increased, and ACD and VCD decreased significantly with increasing accommodation (all p ≤ 0.02). A longer baseline AL was associated with greater levels of accommodation‐induced axial elongation at the 9 D demand ( p < 0.0001). Conclusions: AL increased significantly during accommodation in children, consistent with previous findings in adults up to a 6 D demand. AL continued to increase for higher levels of accommodation (9 D demand), which children may experience during near tasks. These findings provide further insights into potential mechanisms linking near work, axial elongation, and myopia development. However, no myopic children participated in this experiment; therefore, further research is required.